Influencia de la calidad del servicio en la satisfacción de los pacientes de la Clínica Dermika, Trujillo - Avalos Murga, Cecilia Beatriz (2017)
The present research work is entitled "INFLUENCE OF QUALITY OF SERVICE IN THE SATISFACTION OF PATIENTS OF CLINIC DERMIKA, TRUJILLO" in a way that allows us to ask the following question How does the quality of service influence patient satisfaction At the DERMIKA clinic in the city of Trujillo? This is the basis for the performance of the work, so that it will allow us to find out how much the quality of service influences in the satisfaction of the patients of the city of Trujillo, because this factor plays a very important role in the behavior of patients At the time of being attended at the clinic DERMIKA of the city of Trujillo, the following hypothesis is proposed: Quality of service influences generating an average degree of satisfaction in the patients of the clinic DERMIKA, Trujillo. The design and technique used for data collection and processing is as follows: Cross-Sectional Design and the quantitative technique to be used is the application of the survey, once performed and applied it was concluded in the following: Quality of services presents A medium degree of influence in the satisfaction of the patients of the DERMIKA clinic of the city of Trujillo, which verifies how much can influence the appropriate handling of the times of being attended to each patient for the fulfillment of the schedules cited and for this purpose Develops satisfaction strategies in the medium and long term.